Extracellular Vesicles in Non-alcoholic Fatty Liver Disease and Alcoholic Liver Disease - Wu, Dongqing; Zhu, Huaqing; Wang, Hua (Frontiers in Physiology, 2021)
As the largest vital solid organ in the body, liver is consisting of multiple types of cells including hepatocytes, Kupffer cell, hepatic stellate cells (HSCs), liver sinusoidal endothelial cells and other immune cells. The communication between these cells is critical in maintaining liver function homeostasis, and dysregulation of such communication contributes to the pathogenesis of various liver diseases. Extracellular vesicles (EVs), including exosomes and ectosomes, act as important mediators of cell-to-cell communication. EVs can be produced and uptaken by a wide range of cells including all types of cells in the liver. Growing evidences show that EVs are involved in the development of liver diseases, especially non-alcoholic fatty liver disease (NAFLD) and alcoholic liver disease (ALD). In this review, we will summarize recent advance in how EVs production are altered in NAFLD and ALD and how the changes of EVs quantity and cargos influences the progression of these diseases. The therapeutic and diagnostic potential of EVs in NAFLD and ALD will be also discussed in this review.